REFLECTIONS ABOUT THE SAMENESS OF HUMAN RIGHTS ONLINE AND OFFLINE - Crnić-Grotić, Vesna; Maslo Cerkic, Sejla; Milašiūtė, Vygantė; Pajuste, Tiina; Susi, Mart (Pravni zapisi, 2024)
The article explores whether and how the concept of the sameness of human rights online and offline can be justified. The comparative method analyzes changes in the meaning and scope of four human rights when transposed from the nondigital to the digital domain: the right to education, nondiscrimination, freedom of expression, and privacy (emphasizing the right to be forgotten). These rights are examined through shifts in meaning, related state duties, and the role of private actors. The theoretical framework is the non-coherence theory of digital human rights, which asserts that online and offline human rights align only at a general level. As the scope and meaning of rights become more specific, they diverge, though the abstract concept of sameness remains. This generic feature of human rights supports the argument that they are domain-independent.